Combined puncture/cutting of elastomer membranes by pointed blades: An alternative approach of fracture energy. (June 2016) - Triki, Ennouri
Abstract: Resistance to combined puncture and cutting is controlled by two energies, one is the fracture energy or the intrinsic strength of the material, the other reflects the friction energy between a pointed blade and the material. The purpose of this study is to propose an alternative approach derived from the fracture mechanics theory to calculate the fracture energy associated to the puncture/cutting of neoprene rubber by pointed blades. The proposed approach is also based on the application of a sample pre-strained during the puncture/cutting test in order to remove the contribution of friction. It was validated with two different pointed blade angles of 22.5° and 35°. Results show that for an applied pre-strain energy (or tearing energy) of high value, the friction between pointed blade and material is completely removed. Without friction, the total fracture energy is constant. In that case, the crack growth contribution of the applied pre-strain energy is marginal. Growth of the crack is thus completely caused by the puncture/cutting by a pointed blade. Finally, results suggest that the value of the fracture energy corresponding to puncture/cutting by pointed blades is obtained at a frictional contribution of zero, but not at tearing energy value of zero. The value obtained is three times higher than the cutting energy corresponding to a cut by razor blade and also larger than that obtained from puncture by medical needles. Graphical abstract: